Left Atrium Function: Can We Really Predict Outcomes After Catheter Ablation for Atrial Fibrillation? - Alina Yu. Tymoshenko (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Atrial fibrillation (AF) is the most common heart rhythm disorder, affecting 1–2 % of the adult population. AF significantly increases the risks of stroke, heart failure, and overall mortality [1]. Catheter ablation (CA) for AF is considered the gold standard for arrhythmia control in patients with ineffective drug therapy. Determining the functional state of the left atrium (LA) is critical for predicting ablation outcomes.Aim. To evaluate the functional state of the left atrium in patients with AF using speckle tracking echocardiography (STE) and to analyse its prognostic value for catheter ablation results.Materials and methods. Two-dimensional transthoracic echocardiography with speckle tracking was used to assess the functional state of the LA. For detailed assessment, the LA volume index, LA ejection fraction, and LA strain indicators (reservoir, conduit, and contractile deformation) were measured. Reference values were taken from the HUNT study published in 2023 [17]. Between June and December 2024, 24 patients treated for AF at Amosov NICVS were evaluated at the preoperative stage. The mean LA volume was 81.2 ± 22.0 ml, the mean LA ejection fraction was 49.2 ± 12.9 %, and the LA volume index (LAVI) was 40.0 ± 10.3 ml/m². The mean values of reservoir, conduit, and contractile functions were: LASr 23.0 ± 10.2%, LAScd –13.8 ± 5.5 %, and LASct –9.2 ± 6.1 %, respectively.Results. In the study group, the reservoir, conduit, and contractile functions of the LA were lower than the reference values reported in the HUNT study. The mean follow-up period was 4.9 months, and the relapse rate was 16.7 % (4 patients).Conclusions. Assessment of the functional state of the LA using speckle tracking echocardiography may serve as an alternative diagnostic method to predict long-term outcomes after catheter ablation for AF.